Analysis of tensile strength of composite fiber reinforced with areca Nut Skin Fiber using BQTN 157 EX Resin - Safriwardy, Ferri; Rizki, Muhammad Nuzan; Masrullita, Masrullita; Simbolon, Muhammad Iqbal (International Journal of Trends in Mathematics Education Research, 2023)
In the development of materials science, especially polymers, natural fibers such as areca nut shell fiber are increasingly attractive to use. The use of synthetic polymer materials made from fiber can replace conventional materials such as metal, wood and leather. They can replace conventional materials with the advantages of lower price, environmental friendliness, and recyclability. Areca nut shell fiber, as an example of a natural fiber, has great potential in the furniture industry, crafts, and as an ingredient in traditional medicine. This fiber is used as a reinforcing material in composites with an Unsaturated Polyester Yukalac resin matrix. Unsaturated Polyester Yukalac resin, with characteristics such as stiffness, flexibility, water resistance, chemical resistance and weather resistance, is used as a matrix in making composites. The aim of this research is to make a plastic composite prototype reinforced with areca palm fiber, varying the volume fraction of areca nut shell fiber by 30%:50%, 50%:60%, 70%:70%, 90%:80% and for the matrix using polyester resin. BQTN 157 EX. The fiber composition is arranged in a mold in the same direction using the hand lay up method. Composite testing is in the form of a tensile test referring to the ASTM 638-03 standard. The results of the largest tensile testing process were with a volume fraction of 50% with an average value of 7.11 MPa, and for tensile testing the lowest was a volume fraction of 70% with an average value of 6.17 MPa, it can be concluded for reinforced plastic composites Areca nut shell fiber has considerable ability to be applied as a structural material. This is a step towards the development of innovative and environmentally friendly composite materials for various industrial applications.